Inheritance of M.G. Chernyahovski, the first head of faculty of general surgery, Rostov state medical university from his book «Surgical pathology and therapy» - V. N. Chernov; A. I. Maslov (Медицинский вестник Юга России, 2011)
The article analyzes Prof. M.G. Chernyahovski’s ideas: the role of general surgery in the training of doctors of various specialties, the need by the surgeon to know the pathogenesis of human illness, the original name of surgery: «therapeutical surgery» that the surgeon should not only remove organs but also treat the patient.